2014
DOI: 10.1590/0074-0276130230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characterisation of HTLV-1 and 2 dual infections in patients with pulmonary tuberculosis in Central-West Brazil

Abstract: Human T-cell lymphotropic virus (HTLV) may impact the clinical course of tuberculosis (TB). Both infections are highly endemic in Brazil. The aim of this study was to assess the prevalence of HTLV-1/2 in TB patients in Central-West Brazil and to perform a genetic characterisation of the respective isolates. Of the 402 patients, six (1.49%) were positive for anti-HTLV and five (1.24%; 95% confidence interval: 0.46-3.05) were infected with HTLV-1/2. Genetic characterisation demonstrated that the four HTLV-1 isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…The prevalence of HTLV‐1 (0.59 per 1000; 95% CI: 0.38‐0.87) found in this study was in line with rates demonstrated for other blood donors in Brazil (0.2‐1.1 per 1000) . All HTLV‐1 isolates from this study were classified as belonging to the Transcontinental (A) subgroup of the Cosmopolitan (1a) subtype, highlighting that this subtype is endemic in Piauí, as well as in the whole country …”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of HTLV‐1 (0.59 per 1000; 95% CI: 0.38‐0.87) found in this study was in line with rates demonstrated for other blood donors in Brazil (0.2‐1.1 per 1000) . All HTLV‐1 isolates from this study were classified as belonging to the Transcontinental (A) subgroup of the Cosmopolitan (1a) subtype, highlighting that this subtype is endemic in Piauí, as well as in the whole country …”
Section: Discussionsupporting
confidence: 87%
“…This was also demonstrated in the Northeast Region of Brazil ( Moreira et al, 1993 ; Pedral-Sampaio et al, 1997 ; Marinho et al, 2005 ; Bastos et al, 2009 ) and in a study conducted in the Central-west region of Brazil, where the prevalence was higher than that observed in blood donors ( Kozlowski et al, 2014 ). In a study conducted with patients admitted to a hospital in Salvador, Brazil, 2 deaths were observed in HTLV-1 and tuberculosis coinfected patients ( Bastos et al, 2012 ).…”
Section: Htlv-1/tuberculosis Coinfection and Atl/lmentioning
confidence: 56%
“…The high prevalence of HTLV-1 among patients with pulmonary tuberculosis (PT) ( Moreira et al, 1993 ; Pedral-Sampaio et al, 1997 ; Marinho et al, 2005 ; Verdonck et al, 2008 ; Bastos et al, 2009 ; Kozlowski et al, 2014 ), high mortality rates among co-infected individuals, and increased likelihood of hospitalization and treatment for PT in patients with HTLV-1 ( Bastos et al, 2012 ) reinforce the hypothesis that individuals with HTLV-1 are at higher risk of infection with Mycobacterium tuberculosis ( Marinho et al, 2005 ; Grassi et al, 2016 ).…”
Section: Htlv-1/tuberculosis Coinfection and Atl/lmentioning
confidence: 99%
“…A study conducted in São Paulo found a rate of 20.7% for HTLV-2a/b 13 and a rate of 0.24% for HTLV-2a/c was found in a population of the central-western region of Brazil in patients co-infected with pulmonary tuberculosis. 8 …”
Section: Discussionmentioning
confidence: 99%
“…HTLV-2 is endemic in some Indian villages and urban populations in northern Brazil, 7 in the state of São Paulo and in the central western region of the country. 8 …”
Section: Introductionmentioning
confidence: 99%